Manajemen Kemiskinan Inklusif dalam Perspektif Pembangunan BerkelanjutanThis study aims to systematically review the inclusive poverty management approach from a sustainable development perspective, emphasizing the importance of integrating social, econom - Andi, Andi; Hijrana, Hijrana (Visi Pencerah Nusantara, 2024)
This study aims to systematically review the inclusive poverty management approach from a sustainable development perspective, emphasizing the importance of integrating social, economic, ecological, and spatial dimensions in policy design. Although various studies have highlighted the relationship between poverty, community resilience, and social inclusion, sectoral, non-participatory, and ahistorical approaches still dominate and fail to address the structural roots of inequality. This study uses a qualitative method with a Systematic Literature Review (SLR) approach, which identifies and evaluates scientific publications from the Dimensions and Scopus databases during the period 2020–2025. Selection criteria include reputable, relevant publications, available in full text, and written in Indonesian or English. The results of the review show that the effectiveness of inclusive poverty management is greatly influenced by the application of the principle of intersectionality, meaningful participation of vulnerable groups, and contextual socio-ecological resilience to global crises. This study provides a conceptual contribution to the development of a responsive, equitable, and sustainable cross-sectoral intervention model. These findings reinforce the urgency of formulating transdisciplinary policies that bridge poverty reduction, climate resilience, and local economic revitalization within the framework of achieving the Sustainable Development Goals (SDGs).